INTERNALISASI NILAI-NILAI TASAWUF DALAM SHALAWAT WAHIDIYAH BAGI PEMBENTUKAN KARAKTER MULIA (STUDI KASUS DI SMK IHSANNIAT REJOAGUNG NGORO JOMBANG) - Rofiatul Hosna (IAIN Padangsidimpuan, 2018)
The purpose of this research is to know about the process of internalizing the values of Sufism in Shalawat Wahidiyah in SMK Ihsanniat Rejoagung Ngoro Jombang in shaping the character of their students. This study used a qualitative approach with the design of field research. The data collection techniques used: (1) observation, (2) interviews, and (3) documentation. Data were analyzed by data collection, data reduction, data presentation, drawing conclusions/verification. The results were obtained: First: practice activities Salawat Wahidiyah commonly known by the term Mujahadah. Second: The process of internalization of the values of Sufism Salawat Wahidiyah including through: Through Mujahadah that routinized, Prompts always read Nida 'either verbally or silently, Material kewahidiyahan and integration with other materials, training or upgrading Kewahidiyahan, GSDB (Movement conscious of giving box), Habits and models, and study the book of al-Hikam. Third : Generally, Characters students as a result of the internalization of Sufism Shalawat Wahidiyah in SMK Ihsanniat is good. Their character can be seen from several aspects: Attitude, emotions, beliefs, habits and self-conception. Fourth the environment, teachers and staff employees are compact, The spirit of the teachers and students, and Innovation Master Kewahidiyahan. While the inhibiting factors are: Facilities and infrastructure are inadequate, some outside students who have not become followers Wahidiyah, majority of teachers do not practice the Shalawat Wahidiyah and less administrative competencies of kewahidiyahan teacher